Evaluación del efecto de fertilización, aplicación de estiércol y absorción de elementos en el rendimiento de la secuencia papa-kiwicha, evaluado mediante la técnica del elemento faltante - Alaluna G., Edgardo (2000)
This trial was established to study the effects of foliar fertilization, incorporation of manure and soil application of N, P, K, Mg, Fe, Mn and Zn; these nutrients were evaluated through the missing element technique. The trial was conducted in a sandy soil from central coast of Peru. Potato and kiwicha were used as test plants, the latter being used to evaluate the residual effect in each treatment. Soil fertilization for each element in mg. kg-1/pot were 200 =N, pps and K2 0; 50 =MgO and Fe and 25 =Mn and Zn. A complete randomized design with factorial arrangement and three replications was used. Replications were 4 kg soil pots. The evaluation consisted in measuring the total dry matter yield and total nutrient uptake in the potato-kiwicha. Applying 25 tn/ha of manure makes possible to supply the nutritional requirements of Fe, Mn and Zn for potato crop. It also partially supplies the requirements of K and Mg and in a very limited extension, P and N requirements. In kiwicha crop, the complete treatment showed a slight yield depression as compared with omitted Mg, K, Mn and P as these elements were enhanced by last year manure mineralization. Manure applications significantly enhanced the N, Mn, P, K, Zn and Fe availability, which increased the total dry matter yield in kiwicha by 1025, 42 and 13% as compared with no manure treatments, and showed a deppresive effect compared with omitted Mn, Zn and Fe, due to the complexing of these elements with organic matter. Foliar fertilization showed a positive effect only in treatments with adequate soil nutritional imbalance as in complete treatment, test and omitted microelements treatments. A significantly positive effect was observed in manure treatments in macro and microelement uptake in potato. In kiwicha, this effect was not clear and only enhanced significantly the phosphorus uptake. Foliar fertilization enhanced the uptake only in treatments with an adequate soil nutrient in balance.